Cultural development, information society and youth's role / Ismail Sualman - Sualman, Ismail (Kolej Cempaka Kenanga, UiTM Shah Alam, 2001)
This article begin with a mple introduction that clearly elaborates about transformation and changes in cultural and information technology. Ideology had been clearly elaborate through the different period of time where the youth are relate to the information society and time. Information society that had influence surf life today had been elaborate deep as establishment of information super highway and multimedia. Relation between development of social culture, information society and young adult had been clearly mention as the 21st century need new values in addition with tolerance, creativity, transparency in management, solidarity and compassion. In this new millennium young adult must take the lead in the construction of new culture. The individual who are creative and tolerance they will participate in this information society easier and will be the master of open system called informationization.